Deposition of Triterpenoids and Steroids in Cuticular Waxes of Representative Fruits of Rosaceae Family during Their Development and Maturation - Dashbaldan, Soyol; Paczkowski, Cezary; Szakiel, Anna (New Innovations in Chemistry and Biochemistry Vol. 5, 2021)
The process of fruit ripening involves many chemical changes occurring not only in the mesocarp but also in the epicarp, including changes in triterpenoid and steroid content of fruit cuticular waxes that can modify the susceptibility to pathogens and mechanical properties of the fruit surface. However, the understanding of the relationships between fruit cuticular composition, ripening-associated changes and the resulting fruit traits, including post-harvest quality, is still preliminary. Meanwhile, the cuticular composition and developmental patterns could have a great impact on cultivation and post-harvest strategies, such as reducing the utilization of pesticides and artificial fruit coatings. The Rosaceae family is one of the major angiosperm families with many economically important fruit crops. Therefore, the aim of the study was the determination of the ripening-related changes in triterpenoid and steroid content of fruit cuticular waxes of three representative plant species from the Rosaceae family, including rugosa rose (Rosa rugosa), black chokeberry (Aronia melanocarpa var. “Galicjanka”) and apple (Malus domestica var. “Antonovka”). The triterpenoid and steroid content in chloroform-soluble cuticular waxes was determined by a GC-MS/FID method at four different phenological stages. The profile of identified compounds was rather similar in selected fruit samples with triterpenoids of ursane-, oleanane- and lupane-type carbon skeletons, prevalence of ursolic acid and the composition of steroids. Increasing accumulation of triterpenoids and steroids, as well as the progressive enrichment of the composition of these compounds in fruit cuticular wax, were observed. The changes in triterpenoid content resulted from modifications of metabolic pathways, particularly hydroxylation and esterification, that can alter interactions with complementary functional groups of aliphatic constituents and lead to important changes in fruit surface quality.